Development of solar powered air inflated grain dryer - DUBEY, ABHINAV; SHARMA, P K; MANI, INDRA (The Indian Journal of Agricultural Sciences, 2019)
Cereals are generally harvested at 20-23% moisture content in order to avoid shattering losses while harvest. Their milling and long term storage is done at lower moisture content which is achieved by drying immediately after harvest. A solar powered air inflated grain dryer was designed and developed for drying of paddy. The developed dryer performance was evaluated by drying freshly harvested paddy with initial moisture content 22Â±0.3% (w.b.) in comparison to sun drying. The developed dryer had a significant difference in temperature of the drying air and drying rate compared to sun drying. The time required for drying of paddy up to milling moisture content of 14% in the developed dryer ranged from 7.5-9 hr and 11-12.8 hr in sun drying respectively. Least square mean values of thermal efficiency, temperature rise in the drying air and drying rate of the developed dryer varied from 18.7-45.7%, 3.35-5.81Â°C and 0.36-0.98 kg/hr respectively. The developed solar powered air inflated dryers provide a promising alternative for on farm drying of grains because of its low cost of construction, easy operation, green energy utilization and portability.